(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
When changing the shape of a projectile in order to reduce its ricochet effect when encountering a water environment, its ballistic characteristics during its movement in the air are also altered, such as projectile speed, range, ballistic coefficient, and shooting grouping. The present study aims to determine the influence on the projectile's speed and ballistic coefficient of the radial rings made on its ogive part.